Exosomes Could Offer New Options to Combat the Long-Term Complications Inflicted by Gestational Diabetes Mellitus - Floriano, Juliana Ferreira [UNESP]; Willis, Gareth; Catapano, Francesco; Lima, Patricia Rodrigues de [UNESP]; Duarte Souza Reis, Fabiana Vieira [UNESP]; Pascon Barbosa, Angelica Mercia [UNESP]; Cunha Rudge, Marilza Vieira [UNESP]; Emanueli, Costanza (Mdpi, 2020)
Gestational diabetes Mellitus (GDM) is a complex clinical condition that promotes pelvic floor myopathy, thus predisposing sufferers to urinary incontinence (UI). GDM usually regresses after birth. Nonetheless, a GDM history is associated with higher risk of subsequently developing type 2 diabetes, cardiovascular diseases (CVD) and UI. Some aspects of the pathophysiology of GDM remain unclear and the associated pathologies (outcomes) are poorly addressed, simultaneously raising public health costs and diminishing women's quality of life. Exosomes are small extracellular vesicles produced and actively secreted by cells as part of their intercellular communication system. Exosomes are heterogenous in their cargo and depending on the cell sources and environment, they can mediate both pathogenetic and therapeutic functions. With the advancement in knowledge of exosomes, new perspectives have emerged to support the mechanistic understanding, prediction/diagnosis and ultimately, treatment of the post-GMD outcomes. Here, we will review recent advances in knowledge of the role of exosomes in GDM and related areas and discuss the possibilities for translating exosomes as therapeutic agents in the GDM clinical setting.
Keywords: gestational diabetes mellitus; outcomes; urinary incontinence; therapy; exosomes; microRNAs